Genre taxonomy A knowledge repository of communicative actions. - Yoshioka, Takeshi; Herman, George; Yates, JoAnne; Orlikowski, Wanda
We propose a genre taxonomy as a knowledge repository of communicative structures or "typified actions" enacted by organizational members. The genre taxonomy is intended to help people make sense of diverse types of communicative actions and provide ideas for improving work processes that coordinate the communication of information. It engages several features to achieve this objective. First, the genre taxonomy represents the elements of both genres and genre systems as embedded in a social context reflecting the communicative questions why, what, who, when, where, and how (5W1H). In other words, the genre taxonomy represents the purpose, content, participants, timing, location, and form of communicative action. Second, the genre taxonomy distinguishes between widely recognized genres such as a report and specific genres such as a particular company's technical report, because the difference sheds light on the context of genre use. Third, the genre taxonomy represents use and evolution of a genre over time to help people understand how a genre is used and changed by a community over time. Fourth, the genre taxonomy represents aspects of information coordination via genres, thus providing ideas for improving work processes using genres. We have constructed a prototype of such a genre taxonomy using the Process Handbook, a process knowledge repository developed at MIT. We have included both widely recognized genres such as the memo and specific genres such as those used in the Process Handbook itself. We suggest that this genre taxonomy may be useful in the innovation of new document templates or methods for communication because it helps to clarify different possible uses of similar genres and explicates how genres play a coordination role among people and between people and their tasks.
Keywords: Genre; Genre systems; Grammar; Information search and retrieval; Taxonomy